Навчально-тренувальний процес у школі вищої спортивної майстерності та формування готовності до професійного самовизначення після спорту - Романовський, Олександр Георгійович; Арабаджи, Тимур Дмитрович (Класичний приватний університет, 2016)
У статті зазначено, що навчально-тренувальний процес сприяє розвитку низки особистісних якостей спортсменів, які будуть для них корисними та допоможуть досягти успіху в будь-якій новій сфері професійної діяльності після закінчення спортивної кар’єри. Проте наголошено, що розвиток цих якостей є недостатнім для формування готовності спортсмена до нового професійного самовизначення. Необхідною визнано цілеспрямовану роботу: розробку та впровадження в навчально-тренувальний процес педагогічної технології формування готовності до професійного самовизначення спортсменів після закінчення спортивної кар’єри.

According to the humanistic approach it is important that all coaches and higher sportsmanship schools’ administration take care about sporting achievements and the development of the athlete’s personality in general as well. One of the targeted objectives of the educational and training process in schools should be formation of readiness for professional self-determination of athletes after sport career. An athlete, who feels care about himself and his future, gets motivation to reach new sports tops and an opportunity to be a successful person in his after-sport activity. The problem of professional self-determination is especially actual not only for sportsmen but for the whole society. The specific of the educational and training process includes the opportunity to develop personal qualities, which would be useful for an athlete in any new professional sphere after sport career. These qualities are: operability, perseverance, willpower, discipline, effective communication and group interaction. The listed above character traits are developed successfully in the educational and training process. The educational and training process contributes to the development of a number of athlete’s personal characteristics that are the driving force for success in his professional activities after sport career. However, the development of these qualities is not sufficient for the formation of the athlete’s readiness for a new professional identity. The necessary targeted work is development and implementation of pedagogical technology of formation the readiness for athletes’ professional self-determination after sport career to the educational and training process.
The Educational and Training Process in the School of Higher Sportsmanship and Formation of Professional Self-Determination Readiness in After-Sports Activity
Keywords: психологія; працьовитість; наполегливість; сила волі; дисциплінованість; групова взаємодія; комунікація; педагогічна технологія; закінчення спортивної кар’єри; training process; operability; perseverance; willpower; discipline; group interaction; effective communication; professional self-determination; sport career